Point-of-Care Screening for a Current Hepatitis C Virus Infection: Influence on Uptake of a Concomitant Offer of HIV Screening. Issue 1 (December 2018) - Geretti, Anna; Austin, Harrison; Villa, Giovanni; Hungerford, Dan; Smith, Colette; Davies, Paula; Williams, Jillian; Beloukas, Apostolos; Sawicki, Wojciech; Hopkins, Mark
Abstract Eliminating hepatitis C as a public health threat requires an improved understanding of how to increase testing uptake. We piloted point-of-care testing (POCT) for a current HCV infection in an inner-city Emergency Department (ED) and assessed the influence on uptake of offering concomitant screening for HIV. Over four months, all adults attending ED with minor injuries were first invited to complete an anonymous questionnaire then invited to test in alternating cycles offering HCV POCT or HCV+HIV POCT. Viral RNA was detected in finger-prick blood by GeneXpert. 814/859 (94.8%) questionnaires were returned and 324/814 (39.8%) tests were accepted, comprising 211 HCV tests and 113 HCV+HIV tests. Offering concomitant HIV screening reduced uptake after adjusting for age and previous HCV testing (odds ratio 0.51; 95% confidence interval [CI] 0.38–0.68; p < 0.001). HCV prevalence was 1/324 (0.31%; 95% CI 0.05–1.73); no participant tested positive for HIV. 167/297 (56.2%) POCT participants lived in the most deprived neighbourhoods in England. HCV RNA testing using finger-prick blood was technically feasible. Uptake was moderate and the offer of concomitant HIV screening showed a detrimental impact on acceptability in this low prevalence population. The findings should be confirmed in a variety of other community settings.